Altered peptide ligand vaccination with Flt3 ligand expanded dendritic cells for tumor immunotherapy - Fong, Lawrence (The National Academy of Sciences, 2001)
Most tumor-associated antigens represent self-proteins and as a result are poorly immunogenic due to immune tolerance. Here we show that tolerance to carcinoembryonic antigen (CEA), which is overexpressed by the majority of lethal malignancies, can be reversed by immunization with a CEA-derived peptide. This peptide was altered to make it a more potent T cell antigen and loaded onto dendritic cells (DCs) for delivery as a cellular vaccine. Although DCs are rare in the blood, we found that treatment of advanced cancer patients with Flt3 ligand, a hematopoietic growth factor, expanded DCs 20-fold in vivo. Immunization with these antigen-loaded DCs induced CD8 cytotoxic T lymphocytes that recognized tumor cells expressing endogenous CEA. Staining with peptide-MHC tetramers demonstrated the expansion of CD8 T cells that recognize both the native and altered epitopes and possess an effector cytotoxic T lymphocyte phenotype (CD45RA(+)CD27(−)CCR7(−)). After vaccination, two of 12 patients experienced dramatic tumor regression, one patient had a mixed response, and two had stable disease. Clinical response correlated with the expansion of CD8 tetramer(+) T cells, confirming the role of CD8 T cells in this treatment strategy.